Energy Harvesting from Household Heat Sources using a Thermoelectric Generator Module - S. O. Giwa, C. Nwaokocha, A. Layeni, O. Olaluwoye (Nigerian Journal of Technological Development, 2019)
Inefficiency in energy usage has led to the subject of energy harvesting which simply means recycling dissipated waste energy into another useful form of energy. This paper presents the harvesting of waste thermal energy from household heat sources (kerosene stove and generator exhaust pipe) as an electrical energy. Thermoelectric generator (TEG) modules (TGM-161-1.2-2.0) and aluminium heat sinks were constructed and placed close to the heat sources for waste heat harvesting. The hot and cold side temperatures of the TEG modules were measured along with the corresponding output voltages and currents, while the power and energy harvested were estimated. The harvesting of energy from the stove yielded means of 1.532 ± 0.091 V, 0.388 ± 0.003 A, 0.597 ± 0.039 W and 536.87 ± 34.98 J, subject to an average temperature difference of 84.59 ± 3.64 °C. For the generator exhaust pipe, average values of 1.28 ± 0.074 V, 0.285 ± 0.007 A, 0.367 ± 0.029 W and 330.62 ± 26.15 J with an average temperature difference of 62.31 ± 4.88 °C were achieved. The obtained results agreed with previous studies on energy harvesting using TEG modules. This work revealed the potential of waste heat energy harvesting using TEG technology.